2010
DOI: 10.1177/0013916509336813
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Classroom Acoustics on Performance and Well-Being in Elementary School Children: A Field Study

Abstract: Children are more impaired than adults by unfavorable listening conditions such as reverberation and noise. Nevertheless, the acoustical conditions in classrooms often do not fit the specific needs of young listeners. This field study aimed to analyze the effects of classroom reverberation on children's performance and well-being at school. Performance and questionnaire data were collected from 487 children from 21 classrooms which differed in mean reverberation time from 0.49 to 1.1 seconds. Significant effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
119
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(129 citation statements)
references
References 66 publications
6
119
1
3
Order By: Relevance
“…In fact, effects of irrelevant speech on children's listening comprehension and phonological processing have recently been reported (Klatte et al, 2007). Furthermore, field studies have shown that chronic exposure to irrelevant sounds, i.e., indoor noise in classrooms, has enduring effects on children's language, prereading skills, and academic attainment (Klatte et al, 2009;Maxwell & Evans, 2000;Shield & Dockrell, 2008). In order to prevent such outcomes, optimal interior acoustics in the classrooms as well as pedagogical interventions are necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, effects of irrelevant speech on children's listening comprehension and phonological processing have recently been reported (Klatte et al, 2007). Furthermore, field studies have shown that chronic exposure to irrelevant sounds, i.e., indoor noise in classrooms, has enduring effects on children's language, prereading skills, and academic attainment (Klatte et al, 2009;Maxwell & Evans, 2000;Shield & Dockrell, 2008). In order to prevent such outcomes, optimal interior acoustics in the classrooms as well as pedagogical interventions are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of short-term memory in language and reading acquisition on the one hand and its sensitivity to noise-induced disruption on the other hand leads to the prediction that permanent exposure to irrelevant sounds of even moderate intensity may cause enduring deficits in these developmental domains. In fact, field studies have shown that indoor noise in classrooms affects children's language and reading acquisition (Klatte, Hellbrü ck, Seidel, & Leistner, 2009;Maxwell & Evans, 2000;Shield & Dockrell, 2008). Thus, experimental studies on the ISE in children are important in order to construct acoustic environments suitable for learning.…”
mentioning
confidence: 99%
“…The research has shown that a poor acoustic environment has a negative influence upon teaching, learning, and teachers' health. [11][12][13][14][15] However, most of this research has focused on primary/elementary schools. Far less is known about the acoustic quality of secondary/high schools and the impact of noise and poor acoustics upon children of secondary school age.…”
Section: Introductionmentioning
confidence: 99%
“…Impairs cognitive performance in schoolchildren [2][3][4][5][6][7], as well as stress or voice problems for teachers [8,9] can be caused by both the noise coming from outside or inside the classrooms. Indeed, several studies shown that high reverberation and high levels of background noise, due to external or internal noise, can seriously affect speech perception, short-term memory, task assignments and general understanding, resulting in a significant negative impact upon school and working performance and an induced hearing threshold shifts in the worst cases.…”
Section: Introductionmentioning
confidence: 99%